Long-term fluctuations of snow cover thickness and maximum snow storage in Gis-Baikal area - E. V. Maksyutova (Лëд и снег, 2015)
The paper describes the variability of snow depth and maximal snow storage at level of biogeographical areas and provinces for the long-term period of 1961–2010. Tendencies of snow depth changes increase in most cases with significant factors of regression, but the changes are rather small, only 0.6–6 cm/10 years. Steady changes of maximal snow storage are positive in the most cases of wood sites. The greatest increase of maximal snow storage on wood sites is noted in the South Siberian mountain and taiga area with 10–21 mm/10 years, and, on the contrary, with 4–8 mm/10 years on field sites of Mid-Siberian taiga area.